Disparities in living donation. Issue 5 (October 2021) - Lopez-Soler, Reynold I.; Garcia-Roca, Raquel; Lee, David D.
Abstract : Purpose of review: Living organ donation provides improved access to transplantation, thereby shortening transplant wait times and allowing for more deceased organ transplants. However, disparity in access to living donation has resulted in decreased rates of living donor transplants for some populations of patients. Recent findings: Though there have been marked improvements in deceased donor equity, there are still challenges as it relates to gender, racial/ethnic, and socio-economic disparity. Improvements in living donation rates in Hispanic and Asian populations are tempered by challenges in African American rates of organ donation. Socio-economic disparity may drive gender disparities in organ donation resulting in disproportionate female living donors. Tailored approaches relating to language-specific interventions as well as directed educational efforts have helped mitigate disparity. Additionally, the use of apolipoprotein1 testing and modifications of glomerular filtration rate calculators may improve rates of African American donation. This review will evaluate recent data in living donor disparity as well as highlight successes in mitigating disparity. Summary: Though there are still challenges in living donor disparity, many efforts at tailoring education and access as well as modifying living donor evaluation and identifying systemic policy changes may result in improvements in living donation rates.